2020
DOI: 10.3390/nu12103207
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Short-Term Fiber Interventions in Arthritis Patients Increase Systemic SCFA Levels and Regulate Inflammation

Abstract: Chronic inflammatory diseases are often initiated and guided by the release of proinflammatory mediators. Rheumatoid arthritis (RA) is caused by an imbalance between the pro- and anti-inflammatory mediators in the joints, thereby favoring chronic inflammation and joint damage. Here, we investigate if short-term high-fiber dietary intervention shifts this towards anti-inflammatory mediators. Healthy controls (n = 10) and RA patients (n = 29) under routine care received daily high-fiber bars for 15 or 30 days, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 56 publications
(64 reference statements)
0
46
0
1
Order By: Relevance
“…Even though no causal link with host-microbiota has been established, the available evidence supports the hypothesis that dysbiosis in the oral and gut microbiota plays a role in the development of rheumatoid arthritis (Zhang et al, 2015;Maeda and Takeda, 2019). Durholz and others established that a durable Firmicutes-to-Bacteroidota ratio that lasted for over 40 days after the fiber intervention reduced proinflammatory cytokines IL-18 while increasing circulating Tregs in rheumatoid arthritis patients (Dürholz et al, 2020) and that a shift of microbial community in favor of Bacteroidota over Firmicutes was associated with low short-chain fatty acids and increased pro-inflammatory response (Dürholz et al, 2020). In agreement, the microbial data used in this analysis revealed that species belonging to the Bacteroides including Bacteroides stercoris, Bacteroides sp.…”
Section: Discussionmentioning
confidence: 90%
“…Even though no causal link with host-microbiota has been established, the available evidence supports the hypothesis that dysbiosis in the oral and gut microbiota plays a role in the development of rheumatoid arthritis (Zhang et al, 2015;Maeda and Takeda, 2019). Durholz and others established that a durable Firmicutes-to-Bacteroidota ratio that lasted for over 40 days after the fiber intervention reduced proinflammatory cytokines IL-18 while increasing circulating Tregs in rheumatoid arthritis patients (Dürholz et al, 2020) and that a shift of microbial community in favor of Bacteroidota over Firmicutes was associated with low short-chain fatty acids and increased pro-inflammatory response (Dürholz et al, 2020). In agreement, the microbial data used in this analysis revealed that species belonging to the Bacteroides including Bacteroides stercoris, Bacteroides sp.…”
Section: Discussionmentioning
confidence: 90%
“…The impact of dietary fibers on the composition and metabolic activity of the gut microbiome further contributes to the anti-inflammatory effect of vegetarian, vegan or Mediterranean diets. In RA patients, a high-fiber diet increases anti-inflammatory shortchain fatty acids, decreases pro-inflammatory cytokines, and favorably alters the gut microbiome composition [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to preclinical models, similar observations were reported following nutritional SCFAs supplementation in healthy humans [ 9 ] and individuals with rheumatoid arthritis (RA) [ 13 , 14 ]. In line with this, it is interesting to mention that several studies linked the composition of the gut microbiome to inflammatory bone loss in RA [ 15 , 16 ], spondyloarthritis, and ankylosing spondylitis [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 64%